The evolutionary history of the genus Seriola and the phylogeography and genetic diversity of S. lalandi (yellowtail) across its distribution range - Swart, Belinda Louisa (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.